Allelopathic effects of invasive alien species Parthenium hysterophorus L. on seed germination of paddy and wheat - Shrestha, Binita; Thapa, Chandra Bahadur (Himalayan Biodiversity, 2018)
The invasive species are the major cause of crop loss, across the globe, mainly due to their allelopathic effects on the growth of crop plants. In this study, we explored the allelopathic effects of Parthenium hysterophorus on germination of two major cereal crops of Nepal, Rice (Oryza sativa) and Wheat (Triticum aestivum). The experiment was conducted at laboratory of Department of Botany, Prithivi Narayan Campus, Pokhara, Nepal during 2017. In laboratory, seeds of rice and wheat were treated with aqueous extracts of P. hysterophorus plant parts viz. root, stem, leaf, inflorescence and whole plant with concentration of 5, 10, 15 and 20%. The experiment was laid out in a complete randomized design (CRD) in a factorial arrangement with three replicates of each test. The result suggests that the effect was more on wheat than on rice. The maximum inhibition in seed germination of rice was recorded by the inflorescence extract however, in wheat seed germination was inhibited by leaf extract. In both rice and wheat, roots were highly affected than shoots because root first encounters the toxic allelochemicals and absorbs it. The highest concentration (20%) of leaf, inflorescence and whole plant extract was found to be most pernicious whereas root and stem were recorded to have little effects.